Solitary Fibrous Tumor of the Vagina with Potentially Malignant Features: A Case Report and Review of the Literature - Asuman Nihan HABERAL REYHAN (Federation of Turkish Pathology Societies, 2018)
Extrapleural solitary fibrous tumors are being increasingly reported. The retroperitoneum, deep soft tissues of the proximal extremities, abdominal cavity, trunk, head and neck are among the most common extraserosal locations reported. A recurrent solitary fibrous tumor involving the vagina of a 25-year-old woman is reported. Microscopically, the tumor was hypercellular and composed of mitotically active spindle cells. Immunohistochemically, the tumor cells were positive for vimentin, CD34, and bcl-2. Four cases of solitary fibrous tumors involving the vagina have been reported previously. To the best of our knowledge, this is the first case with clinical and histological features suggestive of a malignant behavior.